Kuliah Whatsapp #BincangKB Wonogiri, Alternatif Pembinaan Institusi Masyarakat Pedesaan pada Masa Pandemi COVID-19 - Andham Dewi; Rafinata Fasihani; Musthofa Salya Bhara Fitria (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2021)
Family Planning (FP) Cadre is the spearhead of the Indonesia Family Planning Program As adaptation to COVID-19 pandemic, new methods of learning are need to be implemented through the WhatsApp Lecture “#BincangKB Wonogiri. This study is evaluate e-learning through #BincangKB. This research was a pre-experimental study with one-group pre-test post-test approach and quantitative methods. Quantitative data taken from questionnaire about contraceptive knowledge, perceptions of contraceptive myths, and participant evaluation. The sample were 42 respondents. Descriptive analysis and mean difference test using Wilcoxon signed rank test. The results showed that there was significant increase in contraceptive knowledge (8.06%; p <0.05) and perception of contraceptive myths (26.84%; p <0.05). All respondents expressed interest in participating again. Participants also stated they comfortable with this method because of the flexible time, training materials and easy-to-join registration. This e-learning model can be an alternative in the midst of the COVID-19 pandemic. Support from family planning counselor, other stakeholder, as well as partnerships with other parties are needed, for more varied material which suits FP cadres' needs.